2015
DOI: 10.1002/ijop.12129
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of economic and educational change: Cognitive representation in three generations across 43 years in a Maya community

Abstract: We studied the implications of social change for cognitive development in a Maya community in Chiapas, Mexico, over 43 years. The same procedures were used to collect data in 1969-1970, 1991, and 2012-once in each generation. The goal was to understand the implications of weaving, schooling and participation in a commercial economy for the development of visual pattern representation. In 2012, our participants consisted of 133 boys and girls descended from participants in the prior two generations. Procedures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…However, the design of these two studies does not enable us to explore the role of individual sociodemographic factors. However, other studies in this special section do (Manago, 2015;Maynard, Greenfield, & Childs, 2015;Weinstock, 2015;Zeng & Greenfield, 2015).…”
Section: Limitationmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the design of these two studies does not enable us to explore the role of individual sociodemographic factors. However, other studies in this special section do (Manago, 2015;Maynard, Greenfield, & Childs, 2015;Weinstock, 2015;Zeng & Greenfield, 2015).…”
Section: Limitationmentioning
confidence: 90%
“…Greenfield, Maynard, & Childs (2003) used an experimental procedure to trace changes in children's cognitive development over a period of two decades. (In this special section, Maynard, Greenfield, & Childs, (2015) add two more decades to their cross-temporal study of cognitive development.) To our knowledge, these studies are the first experiments to trace changes in children's social development over such a long time span.…”
mentioning
confidence: 99%
“…The results, in general, supported Greenfield's theory. As the societies moved from Gemeinschaft to Gesellschaft, individuals tended to become more abstract in cognition (Maynard, Greenfield, & Childs, 2015), have more subjectivist epistemic thinking (Weinstock, 2015), display more competitive and less cooperative behaviours (Garcia, Rivera, & Greenfield, 2015), express more equalitarian gender-related attitudes (Manago, 2015), perform fewer caregiver grooming behaviours (Thein, 2015) and hold more individualistic values (Zeng & Greenfield, 2015). In some of the studies, the researchers examined the links between the sociodemographic features as suggested by Greenfield (2009) (e.g., engagement in commercial activities, schooling, use of mobile technology, level of urbanisation) and child and youth performance.…”
mentioning
confidence: 99%
“…But, Zeng and Greenfield (, special section) show, in this special section, that Chinese culture, under similar sociodemographic influences, has also become more individualistic in recent decades, even though important aspects of its collectivistic history are still evident. The most powerful sociodemographic driver of value change at a particular time and place will be that ecological feature or those features that is/are changing most rapidly in the specific time period under study. Testing this theoretical tenet, Maynard, Greenfield, and Childs (, special section) show that, over a period of four decades in a Mexican Maya community, increasing numbers of children have taken an abstract approach to visual problem solving and have shown an understanding of novel stimuli. However, the drivers of cognitive change have shifted: from participation in commercial activity in the first two decades to formal education in the second two decades.…”
mentioning
confidence: 99%
“…In terms of research design, some researchers investigate the impact of social change directly, by diachronic methods (more than one historical time point, sometimes called cross‐temporal); others study it indirectly, by synchronic methods (one historical time point). The diachronic studies are: Maynard et al's (, special section) experimental study of three generations of Maya children over 42 years; Garcia, Rivera, and Greenfield's (, special section) experimental studies of Mexican children over a period of 40 years in one location and 20 years in two others; and Zeng and Greenfield's (, special section) automated content analysis of thousands of Chinese books over a period of 40 years. The synchronic studies have research designs utilising intergenerational change (Weinstock , special section), contrasting sociodemographic environments (Manago, special section; Weinstock, , special section) and the subjective structuring of social change (Thein‐Lemelson, special section).…”
mentioning
confidence: 99%